The maestro [videorecording (DVD)] - Herst, C. V.; Berkeley, Xander, 1955-; Marks, Leo; Clarke, Sarah, 1972- (Freestyle, 2019)
The film is a dramatic biopic about famed composer Mario Castelnuovo-Tedesco.